Improving The Quality of Educational Staff at Private University Through Recruitment and Career Development - Walewangko, Stief Aristo; Untu, Hadi Ignatius; Koleangan, Christoforus Adri Pieter; Katuuk, Deitje Adolfien; Usoh, Elni Jeini (International Journal of Information Technology and Education, 2022)
Recruitment and career development of educational staff at private universities sometimes face challenges. The public's impression of the quality of human resources in private universities is influenced by these phenomena. The purpose of this research is to show the model of recruiting and career development of educational staff at private universities, namely De La Salle Catholic University of Manado (UKDLSM), as well as to make recommendations for improving educational staff quality. The research method employed is qualitative, with data collected through observation, interviews, and documentation. Interviews were held with the Head of the Human Resources Development Bureau (PSDM), educational staff at the PSDM bureau, educational staff in three work units, and three job applicant candidates for education staff. The study's results show that (1) UKDLSM already has a recruitment model for education staff, which is contained in the UKDLSM Organizational and Administrative Documents; (2) UKDLSM already has a career development model for educational staff, such as educational staff orientation, skills and capacity building training, and further studies to take the specific positions; (3) Recommendations: the requirement of manpower planning, the implementation of an open recruiting model with internal and external candidates, and implementing frequent and transparent quality audits of education staff